Tumors and Tumor like Conditions of Eye and Ocular Adnexae: A Comprehensive Study of 359 Cases - Choukimath, Sharanabasav M; ., Krishnaprasad; Choukimath, Vaishali; Krishnaprasad, Samhita (Annals of Pathology and Laboratory Medicine, 2020)
Background: The eye is one of the major sensory organs. The present study aims at a comprehensive study of all the tumours and tumour like conditions of eye and ocular adnexae with their relative incidence in Indian population. Methods: All incisional and excisional biopsies of eye and its adnexal organs received in our laboratory between April - 2010 to December - 2018 were included in this study. Result: A total of 350 cases were studied. Among these, lesions constituted are orbital: 37.4%, Conjunctival: 32%, Eyelid: 18.2%, Intraocular: 9.4% and Lacrimal gland: 2.85% of the total cases. Among the orbital lesions, the most common benign tumor was hemangiomas [15.26 %] and malignant tumour was basal cell carcinomas [10%]. In conjunctiva, carcinoma in situ was the most common lesion [51.4%]. Retinoblastoma [66.66%] was the most common in the ocular lesions. Other tumours and tumour like conditions are discussed in the present study. Conclusion: Early histopathological diagnosis and ancillary diagnostic tests like immunohistochemistry will help to reduce destructive surgeries and the morbidity in terms of vision loss, loss of eyeball and cosmetic factors. Present study aids in knowing the incidence and prevalence of tumor and other lesions seen with orbit, and its adnexa and eyeball.